Manufacturing of scaffolds with interconnected internal open porosity and surface roughness. (15th January 2023) - Calore, Andrea Roberto; Srinivas, Varun; Groenendijk, Linda; Serafim, Andrada; Stancu, Izabela Cristina; Wilbers, Arnold; Leoné, Nils; Sanchez, Ane Albillos; Auhl, Dietmar; Mota, Carlos; Bernaerts, Katrien; Harings, Jules A.W.; et al.
Abstract: Manufacturing of three-dimensional scaffolds with multiple levels of porosity are an advantage in tissue regeneration approaches to influence cell behavior. Three-dimensional scaffolds with surface roughness and intra-filament open porosity were successfully fabricated by additive manufacturing combined with chemical foaming and porogen leaching without the need of toxic solvents. The decomposition of sodium citrate, a chemical blowing agent, generated pores within the scaffold filaments, which were interconnected and opened to the external environment by leaching of a water-soluble sacrificial phase, as confirmed by micro-CT and buoyancy measurements. The additional porosity did not result in lower elastic modulus, but in higher strain at maximum load, i.e. scaffold ductility. Human mesenchymal stromal cells cultured for 24 h adhered in greater numbers on these scaffolds when compared to plain additive-manufactured ones, irrespectively of the scaffold pre-treatment method. Additionally, they showed a more spread and random morphology, which is known to influence cell fate. Cells cultured for a longer period exhibited enhanced metabolic activity while secreting higher osteogenic markers after 7 days in culture. Statement of significance: Inspired by the function of hierarchical cellular structures in natural materials, this work elucidates the development of scaffolds with multiscale porosity by combining in-situ foaming and additive manufacturing, and successive porogen leaching. The resulting scaffolds displayed enhanced mechanical toughness and multiscale pore network interconnectivity, combined with early differentiation of adult mesenchymal stromal cells into the osteogenic lineage. Graphical abstract: Image, graphical abstract